Effects of antibiotic therapy on the early development of gut microbiota and butyrate-producers in early infants - Qiu, Jun; Wu, Sha; Huang, Ruiwen; Liao, Zhenyu; Pan, Xiongfeng; Zhao, Kunyan; Peng, Yunlong; Xiang, Shiting; Cao, Yunhui; Ma, Ye; Xiao, Zhenghui (Frontiers in Microbiology, 2025)
BackgroundAntibiotics, as the most commonly prescribed class of drugs in neonatal intensive care units, have an important impact on the developing neonatal gut microbiota. Therefore, comprehending the effects of commonly used antibiotic therapy on the gut microbiota and butyrate-producers in early infants could provide information for therapeutic decision-making in the NICU.ObjectivesTo explore the effects of antibiotic therapy on the early development of gut microbiota and butyrate-producers in early infants.MethodsA total of 72 infants were included in the study. We performed 16S rRNA sequencing on stool swab samples collected from neonatal intensive care unit patients who received amoxicillin-clavulanic acid (AC, n = 10), moxalactam (ML, n = 28) and non-antibiotics (NA, n = 34). We then compared the taxonomic composition between treatment regimens, focusing on differences in butyrate-producers.ResultsOur study showed that there were significant differences in Shannon index (p = 0.033) and Beta diversity (p = 0.014) among the three groups. At the family level, compared with the other two groups, the relative abundance of Clostridiaceae (p < 0.001) and Veillonellaceae (p = 0.004) were significantly higher, while the relative abundance of Enterococcidae (p < 0.001) was significantly lower in the NA group. The relative abundance of Enterobacteriaceae (p = 0.022) in the AC group was greater than that in the other two groups. Additionally, butyrate-producers (p < 0.001), especially Clostridiaceae (p < 0.001), were noticeably more abundant in the NA group. The relative abundance of Clostridiaceae and butyrate-producers were the lowest in the ML group (p < 0.001).ConclusionWe found that antibiotic therapy had an adverse impact on the initial development of gut microbiota and leaded to a reduction in the abundance of butyrate-producers, particularly Clostridiaceae. Furthermore, moxalactam had a more pronounced effect on the gut microbiota compared to amoxicillin-clavulanic acid.